Distribution of Periphyton in the Upstream Section of Citarum River, West Java, Indonesia - Isma Noviana; Tri Dewi Kusuma Ningrum Pribadi; Keukeu Kaniawati Rosada (Jurnal Biodjati, 2020)
Periphyton indeed plays an undeniably vital role as primary producers in the food web within aquatic ecosystems such as rivers. The existence of periphyton will affect the populations of the aquatic organisms at higher trophic level, thus it is interesting to be explored, especially in big rivers like Citarum. This study aimed to explore the distribution of periphyton, including its types and abundance at several stations in the upstream part of Citarum River based on the land use in the riverbanks, in the dry season of 2018. Samples were taken at nine stations, namely Gunung Wayang Springs, Outlet Cisanti at the valley of Mount Wayang, and the connecting tributaries as follows: Cihejo, Cibuni, Cirasea, Cikaro, Cisangkuy, Cikapundung, and Ciwidey. Samples of periphyton were taken from the substrate of stone, wood, plastic, and macrophytes at three sampling points of each station. Periphyton samples were then scraped off from the surface of the substrate, where the deposit would then be filtered using plankton net No.20, preserved with Lugol 1% and subsequently identified. The results showed there were 83 species from 58 genera of both phytoperiphyton and zooperiphyton, classified as periphyton found on the sites. The total abundance of phytoperiphyton ranged between 2.3 x 104 ind/m2 and 1.3 x 108 ind/m2 where the total abundance of zooperiphyton covered from 4.7 x 102 ind/m2 to 3.7 x 105 ind/m2. The highest and the lowest numbers of total abundance of periphyton were shown at stations of Gunung Wayang Spring and Cirasea tributary, respectively.